Variations of reflectance with moisture content in single maize kernels and spinach leaves at wavelength 300 nm to 800 nm - Md Norimi, Amizadillah (2011)
This research describes an optical fiber reflectance technique in determining the moisture content in single maize kernels and spinach leaves in wavelength region from 300 nm to 800 nm. The technique is a simple, fast, non-destructive and accurate way to establish the relationship between reflectance and moisture content of both samples. Spectral acquisitions were controlled using the Ocean Optic Spectra Suite operating software. Samples were illuminated by a light source that combines deuterium and tungsten halogen light sources in a single optical path. The Ocean Optic Spectroscopy system consists of an integrated set of seven 440 μm diameter fibers with six illumination fibers encircling one detection fiber. Spectral changes were related to changes in the apparent colour of maize kernels and spinach leaves as it was influenced by moisture content. The results suggest that the percentage of reflectance decreases with moisture content for both maize kernel and spinach leaves at all wavelengths. Lower values in moisture content will result in a slightly darker colour of both samples which in turn will reduce the percentage values of reflectance. In this work, the actual moisture content was found by applying standard oven drying method whilst the Kubelka-Munk theory was used to characterize the scattering and absorption coefficients of single maize kernels and spinach leaves. The performance characteristics of the optical fiber technique for the determination of moisture content were presented in terms of accuracy, standard deviation, probability density function and tolerance. The relative error of the optical fiber technique to determine moisture content based on reflectance measurements were found to be as low as 0.037 at 590 nm for single maize kernels and 0.073 at 380 nm for spinach leaves.